The Age of Consequences: The Foreign Policy and National Security Implications of Global Climate Change - Campbell, Kurt M.; Gulledge, Jay; McNeill, J. R.; Podesta, John; Ogden, Peter; Fuerth, Leon; Woolsey, R. J.; Lennon, Alexander T.; Smith, Julianne; Weitz, Richard (2007)
Although the consequences of global climate change may seem to be the stuff of Hollywood--some imagined, dystopian future--the melting ice of the Arctic, the spreading deserts of Africa, and the swamping of low lying lands are all too real. We already live in an "age of consequences," one that will increasingly be defined by the intersection of climate change and the security of nations. For the past year a diverse group of experts, under the direction and leadership of the Center for Strategic and International Studies (CSIS) and the Center for a New American Security (CNAS), met regularly to start a new conversation to consider the potential future foreign policy and national security implications of climate change. The group consisted of nationally recognized leaders in the fields of climate science, foreign policy, political science, oceanography, history, and national security.